Perceptions and Attitudes Toward Dementia in Predominantly African American Congregants. (November 2021) - Epps, Fayron; Foster, Kimberly; Alexander, Karah; Brewster, Glenna; Chester, Mia; Thornton, Jacquelyn; Aycock, Dawn
The purpose of this study was to identify the perceptions and attitudes of African American congregants toward dementia before and after attending a dementia-focused workshop. Six churches in Metropolitan Atlanta, Georgia, hosted the workshops. Attendees ( N = 171) participated in a free association exercise to evaluate their perceptions and attitudes toward dementia. Before and after the workshop, participants wrote words and phrases that occurred to them when they thought of dementia. Content analysis was used to identify themes. Before the workshop, participants' responses tended to include negative language (e.g., fear, memory loss, sadness). After the workshop, participants expressed more positive words (e.g., support, hopefulness, caring). These findings suggest that education can change congregants' perceptions about dementia and potentially reduce dementia-associated stigma. This change will allow families to feel comfortable both interacting with and seeking help from those in their faith communities.